Methods for Developing Reading Competence of Secondary School Pupils in English Lessons - Kupaysinova, Zarifa (Indonesian Journal Publisher, 2024)
Reading competence is crucial for academic achievement. Reading competence is linked to success at school and over the life. It is also regarded as one of the most challenging areas, thus any educational institution has to give it greater focus to develop pupils’ reading competence. This article presents the effective reading approaches in order to develop secondary school pupils’ reading competence in English lessons.